Rancang Bangun Aplikasi Typing Test Sebagai Sarana Peningkatan Kemampuan Menulis Digital Teks Arab / Design of Typing Test Application as a Means of Improving Arabic Text Digital Writing Skills - Nurstalis, Raihan; Tatang, Tatang; Supriadi, Rinaldi (IAI DDI Polewali Mandar, Indonesia, 2024)
Digital literacy skills become very important for life as the digital era develops (all digitalization). This is a challenge for Arabic language education students to improve their abilities in the digital field. One of them is digital writing using a laptop/computer. This is the basis of this research. This research aims to build a website-based Arabic typing test application as a means of practicing typing using Arabic letters. The method that researchers use in this research is the Research and Development (R&D) method using the ADDIE model. In the first stage of this research begins with analyzing needs through questionnaires to Arabic language education students at the Indonesian Education University (UPI). Then proceed with the development of the application with the name Pro-Typer.com. Then finally closed with the evaluation stage. This application can be accessed through the Pro-Typer.com link, the link at arab.upi.edu or through search engines such as Google. This application has four things that differentiate it from other applications, the first is the typing learning feature starting from per letter, word, to paragraph. Then the second feature is a test feature based on CEFR standards. Then, an integrated link on the official website of UPI Arabic language education students (arab.upi.edu). and the last is a column of criticism and suggestions.Abstrak: Kemampuan literasi digital menjadi sangat penting bagi kehidupan seiring berkembangnya era digital (serba digitalisasi). Hal tersebut menjadi tantangan bagi mahasiswa pendidikan bahasa Arab untuk meningkatkan kemampuannya di bidang digital. Salah satunya menulis digital menggunakan laptop/komputer. Hal tersebut menjadi dasar dari penelitian ini. Penelitian ini bertujuan untuk membangun aplikasi typing test Bahasa arab berbasis website sebagai sarana berlatih mengetik menggunakan huruf Arab. Metode yang peneliti gunakan dalam penelitian ini adalah metode Research and Development (R&D) dengan menggunakan model ADDIE. Pada tahap pertama penelitian ini dimulai dengan Analisa kebutuhan melalui kuesioner kepada mahasiswa pendidikan bahasa Arab Universitas Pendidikan Indonesia (UPI). Lalu dilanjutkan dengan pembagunan aplikasi dengan nama Pro-Typer.com. Lalu terakhir ditutup dengan tahap evaluasi. Aplikasi ini bisa diakses melalui tautan Pro-Typer.com, tautan di arab.upi.edu ataupun lewat mesin pencari seperti Google. Aplikasi ini memiliki empat hal yang menjadi pembeda dengan aplikasi lain, pertama adalah fitur pembelajaran mengetik dari mulai per huruf, kata, hingga paragraf. Lalu fitur yang kedua adalah fitur test yang berdasarkan standar CEFR. Lalu, tautan terintegrasi di website resmi mahasiswa pendidikan bahasa Arab UPI (arab.upi.edu). Serta yang terakhir adalah kolom kritik dan saran.